2018
DOI: 10.3174/ajnr.a5881
|View full text |Cite
|
Sign up to set email alerts
|

Transdural Blood Supply in Cerebral Arteriovenous Malformations: A Systematic Evaluation of Angioarchitecture

Abstract: BACKGROUND AND PURPOSE: Arterial transdural blood supply is a rare angiographic phenomenon in cerebral AVMs. This study aimed to evaluate angiographic transdural blood supply characteristics and to describe the clinical peculiarities of these lesions. MATERIALS AND METHODS: A prospective AVM data base of 535 patients, enrolled from 1990 to 2016, was analyzed retrospectively. Clinical information was reviewed through patients' medical charts and radiologic studies. Patients with previous AVM treatment were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…In this study, we found that there was no difference in age between the patients with and without a TBS, which was consistent with the study by Stein et al ( 5 ). Of note, we found that patients with higher SM grades tended to have a TBS, which was also consistent with past reports ( 1 , 3 , 5 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we found that there was no difference in age between the patients with and without a TBS, which was consistent with the study by Stein et al ( 5 ). Of note, we found that patients with higher SM grades tended to have a TBS, which was also consistent with past reports ( 1 , 3 , 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…To explore the heterogeneity of TBSs, Stein et al classified TBSs into 3 types based on the proportion and intensity of BAVM nidi perfusion by ECA feeders ( 5 ). In the present study, we divided the TBSs into 3 types according to their sources as follows: TBSs originating from the unilateral ECA and/or VA, TBSs originating from the bilateral ECA and/or VA, and TBSs with involvement of the MHT ( Figures 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations of BAVM with TBS are similar but not identical to those of BAVM without TBS. The blood-supplying artery of a BAVM with TBS involves the dura; thus, the clinical manifestations of the BAVM share the characteristics of the dura (31). However, the major clinical manifestations are associated with the size and location of the BAVM.…”
Section: Clinical Manifestationsmentioning
confidence: 99%